Development of freeze-dried marang (Arto carpus odoratissimeis) - Dimaano, Miguel Angelo D.
ABSTRACT Marang is a fruit with great market potential but the availability of the fruit in its fresh state is very limited due to very fast senescence. This study was undertaken to explore the feasibility of producing a freeze-dried product using marang pulps. The effect of fruit maturity on the quality of the rehydrated marang was determined by physico-chemical analysis and sensory evaluation using 10 untrained panelists. Rehydration capacity of the freeze-dried product was evaluated thereafter and finally, the physico-chemical, microbiological and consumer acceptance test using 35 untrained panelists of the final product was determined. T-test showed that the use of ripe marang pulps was more acceptable to the panel than the rare-ripe in freeze-drying operation. No significant difference was observed on the quality of the marang pulp using one, two or three minutes of rehydration at boiling temperature. For economical reasons, one minute rehydration was sufficient to make the sample acceptable. The freeze-dried marang pulp developed in this study has a pH of 5.91, titrable acidity of 0.069% and 0.276 water activity. Microbial examination of the product showed that the total aerobic count was within the safe limit for dried tropical fruits, however, yeast and mold count exceeded the 102 cfu/g safe limit. Rehydrated marang pulps in general were 'liked slightly' by consumers. Developing a product with great market potential would deliver beneficial effects, but significant sensorial issues in achieving consumer acceptability is needed.